Glazing systems with Parallel Slats Transparent Insulation Material (PS-TIM): evaluation of building energy and daylight performance - Sun, Yanyi; Liang, Runqi; Wu, Yupeng; Wilson, Robin; Rutherford, Peter (Elsevier, 2018)
Being responsible for a significant proportion of total heat loss in façade dominated buildings, the design and specification of the envelope, particularly the building’s glazing system, is a key factor in determining overall energy consumption. To address this, an innovative double glazed façade system comprising parallel transparent/translucent plastic slats sandwiched between the glass panes to form a Parallel Slat Transparent Insulation Material (PS-TIM) system is proposed as a potential solution. This PS-TIM system reduces heat transfer between the glazing panes whilst maintaining access to solar radiation and daylight.